The impact of Covid 19 on family relations in Saudi society - Al-Qathami, Sumaya Mohammed; Asiri, Shatha Hussain (Journal of Humanities & Social Sciences, 2022)
This study aimed to investigate the extent of the impact of Covid-19 on family relations in Saudi society. And determine the relationship between the impact of Covid-19 and a set of variables (such as gender, age, educational level). And determining the extent of the impact of Covid-19 on family relations within the Saudi society. The study sample consisted of (200) Saudi families. The two researchers adopted the social survey method. One of the most important results of the study is the effect of Covid-19 on the relationship between husband and wife, fathers and children in Saudi society was weak. And there were no statistically significant differences for the effect of Covid-19 on family relations according to the educational level variable. Also, there were no statistically significant differences in the impact of Covid-19 on family relations according to the family income variable. It also showed that there were no statistically significant differences in the effect of Covid-19 on the relationship between parents and children according to the variable of the type of marriage. It also showed that there are statistically significant differences in the impact of Covid-19 on family relations according to the variable of the type of marriage in favor of marriage from the vicinity of friends, which means that married people from the vicinity of friends have affected their relationships negatively during Covid-19. And the most important recommendations that came out of the study is to conduct the conferences, symposiums & lectures by the governmental and private associations to raise the community awareness about the relationships within the families and how to manage and respond to crisis by training the individuals on problem solving strategies. Moreover, to emphasis on the role of educational institutes in conducting awareness programs for the students in the schools and universities to assure the importance of family relationships and empower them with the communication skills needed within the family. Added on that, to make more research about the impact of crisis and pandemics on the relationships within the families and its importance in the stability of the family. Finally, to educate the parents about the management of relationships during the crisis and how to create an atmosphere that help to adapt with the reality around.